Structural Change and Spurious Persistence in Stochastic Volatility - Walter Krämer; Philip Messow (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2012)
We extend the well established link between structural change and estimated persistence from GARCH to stochastic volatility (SV) models. Whenever structural changes in some model parameters increase the empirical autocorrelations of the squares of the underlying time series, the persistence in volatility implied by the estimated model parameters follows suit. This explains why stochastic volatility often appears to be more persistent when estimated from a larger sample as then the likelihood increases that there might have been some structural change in between. – – Der bei GARCH-Modellen wohlbekannte Zusammenhang aus Strukturbrüchen und steigender Persistenz wird im Rahmen dieses Artikels auf die Klasse der Stochastic Volatility (SV)-Modelle erweitert. Durch Strukturbrüche vergrößern sich die empirischen Autokorrelationen der quadrierten Beobachtungen der Zeitreihe und mit ihnen die Persistenz. Hieraus folgt, dass die geschätzte Persistenz bei SV-Modellen in der Regel größer wird, je größer das Sample ist, da hierdurch die Wahrscheinlichkeit für einen oder mehrere Strukturbrüche steigt.
Keywords: C32; C58; 330; Persistence; stochastic volatility; structural change